Participatory development of evidence-based patient narrative videos for patients with eating disorders: a methodological approach and pilot data - Melissa-Claire Daugelat; Bettina Gregg; Sophia Helen Adam; Kathrin Schag; Joachim Kimmerle; Katrin Elisabeth Giel (Journal of Eating Disorders)
Abstract Background Patient narratives can best be defined as personal stories of persons previously or currently affected by a physical or mental health disorder. The collaborative development and implementation of such narratives reflects a participatory approach between researchers, patients, and members of the public towards the development of new interventions. Patient narratives can foster feelings of support and belonging, as well as increase hope and motivation towards recovery. Aims of this pilot study were (a) the collaborative development of a series of evidence-based patient narrative videos about eating disorders, (b) their initial evaluation with a group of participants without (current) eating disorders, and (c) to provide a reproducible documentation of this methodological approach. Method A multi-stage participatory process was used including a) a systematic review, b) focus groups with affected persons, c) the participatory narrative development, and d) an initial pilot study with participants without (current) eating disorders. A former and currently recovered patient was recruited as a lived experience representative, while a psychotherapist provided the same information from a professional perspective. Control group videos featured the lived experience representative discussing a somatic condition unrelated to eating disorders (i.e., torn knee ligament). Two videos were created for each perspective with varying degrees of emotionality of the content. Results Nineteen female participants without (current) eating disorders were recruited for the pilot study. All videos received positive ratings, however, participants rated videos in which the lived experience representative discussed her eating disorder as significantly more authentic than the control group videos, as well as significantly more empathic, useful, and better overall than the psychotherapist and control group videos. Participants further indicated a clear preference for videos with higher emotionality, regardless of which perspective or disorder was being presented. Discussion The use of patient narratives for eating disorders is a relatively new methodological approach. This paper provides one example of how evidence-based patient narratives can be constructed. The patient narratives created in this study received positive feedback from participants without (current) eating disorders and are currently being tested in a 4-arm randomised controlled pilot study with patients affected by eating disorders.